ANALISIS EVALUASI STRUKTUR GEDUNG SD UMMU AIMAN KECAMATAN LAWANG KABUPATEN MALANG MENGGUNAKAN METODE RANGKA MOMEN PEMIKUL KHUSUS - Muhammad Zuhdi Irham (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The increasing number of new students studying at SD Ummu Aiman has resulted in a shortage of space in the school building. Therefore, the addition of a new building is required to address this issue. However, the region of Indonesia, especially Java Island, is prone to earthquakes, making it necessary for all infrastructure development to consider earthquake resistance. SD Ummu Aiman's building is no exception, thus requiring special design and supervision to reduce the risk of losses due to earthquake loads that could affect the structure. This case study report will discuss the planning and design of a three-story building made of reinforced concrete for SD Ummu Aiman. In the preparation of this report, the emphasis will be on load analysis, SAP 2000 modeling, and reinforcement control analysis to understand the results of the preliminary structural design and analyze the reinforcement of beam structures using the special moment frame method. The results of the structural design include a 10 cm and 12 cm thick slab with main reinforcement of Æ8-100, the size of the main beams is 35/25 with main reinforcement of 2Æ16 2Æ14 and shear reinforcement of Æ8-150, 25/20 with main reinforcement of 2Æ16 2Æ14 and shear reinforcement of Æ8-120, and the size of secondary beams is 25/20 with main reinforcement of 3Æ25 2Æ25 and shear reinforcement of Æ8-200. The column size is 30/30 with main reinforcement of 4 D16 2 D12 and shear reinforcement of Æ8-150, and 25/25 with main reinforcement of 4 D12 and shear reinforcement of Æ8-150.